Attention-based Convolutional Autoencoders for 3D-Variational Data Assimilation - Mack, Julian; Arcucci, Rossella; Molina-Solana, Miguel; Guo, Yi-Ke (Computer methods in applied mechanics and engineering, 2020)
We propose a new ‘Bi-Reduced Space’ approach to solving 3D Variational Data Assimilation using Convolutional Autoencoders. We prove that our approach has the same solution as previous methods but has significantly lower computational complexity; in other words, we reduce the computational cost without affecting the data assimilation accuracy. We tested our proposal with data from a real-world application: a pollution model of a site in Elephant and Castle (London, UK) and found that we could (1) reduce the size of the background covariance matrix representation by O(103), and (2) increase our data assimilation accuracy with respect to existing reduced space methods. •We propose a new ‘Bi-Reduced Space’ approach to solving 3D Variational Data Assimilation.•We use Convolutional Autoencoders to create the reduced space for solving 3D Var.•We prove that our approach has the same solution as previous methods for reducing 3D Var space.•We prove that our approach has significantly lower computational complexity of previous methods.•We tested the new method with data from a real-world application: a pollution model in London.